Complete mitochondrial genome of the endemic species Korean aucha perch Coreoperca herzi (Teleostei, Centrarchiformes, Sinipercidae). (2nd September 2016) - Park, Chang Eon; Park, Gun-Seok; Kwak, Yunyoung; Hong, Sung-Jun; Khan, Abdur Rahim; Jung, Byung Kwon; Park, Yeong-Jun; Kim, Min-Chul; Kim, Kgu-Hwan; Park, Hee Cheon; Lee, In-Jung; Shin, Jae-Ho
Abstract: In this study, we sequenced the complete mitochondrial genome of the endemic species Korean aucha perch Coreoperca herzi (Teleostei, Centrarchiformes, Sinipercidae). The mitogenome, consisting of 16 495 base pairs (bp), encoded 13 protein-coding genes (PCGs), 2 ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs) and 2 non-coding region. The overall base composition of C. herzi is G + C: 46.3%, A + T: 53.7%, apparently with a slight AT bias. Phylogenetic analysis showed that the C. herzi was closed to Coreoperca kawamebari .